A Meta‐Analysis on the Elasticity of Demand for Pesticides. (14th September 2016) - Böcker, Thomas G.; Finger, Robert
Abstract: There is an increasing policy interest in pesticide taxation schemes as a measure to reduce harmful effects of pesticide use. The effectiveness of such tax depends, however, on the price elasticity of demand for pesticides. Moreover, information on these demand elasticities and their determinants is of crucial relevance for policy‐making and normative modeling approaches. In this article, we present a meta‐analysis based on studies that have estimated pesticide demand elasticities in Europe and North America. Our meta‐analysis reveals that the own‐price elasticities of demand for pesticides are, with a median of −0.28, significantly smaller than zero, but also significantly larger than −1, i.e. to be inelastic. We find that the demand for pesticides for special crops is less elastic than that for arable and grassland. In addition, the demand for herbicides is more elastic than for other pesticides. Studies that consider only short‐term horizons and little flexibility for farmers to adjust to price changes generate significantly less elastic pesticide demands. The results also indicate that more recent studies identify lower pesticide price elasticities of demand. Furthermore, we find that peer‐reviewed studies tend to find more inelastic results compared to grey literature.